Mutual impact of material accumulation on spatial needs, behavioral adjustment, and residential satisfaction a case study on filipino households - Valdehueza, Troy L. (2023)
This study intended to examine the impact of material accumulation on spatial needs, behavioral tendencies, and residential satisfaction models. A mixed-methods approach was implemented through an integrated questionnaire of Residential Satisfaction and Clutter Quality, with spatial mapping, thematic, correlational, and comparative analysis, and the role of material accumulation in the architectural context of a Filipino house was determined. Case studies conducted in Deca Homes Tacunan and Wellspring Village Catalunan Pequen?o, Davao City, revealed the significance of the distribution of setbacks and strategies for the proportion of rooms and fenestration elements in influencing how material accumulates along a family?s life stage. Material accumulation was observed to be more substantial and maximized in single-attached homes. Toys and clothes constitute the majority of material concentration found in most spaces. Flexibility was preferred over fixtures in furniture placements. Adjustment begins before occupancy, wherein a perpetual cycle of negotiation and achieving equilibrium was observed, which was capacitated through a series of self-evaluations. Ultimately, a definite list of most prevalent material accumulation per space was established.Through the recognized findings, it is conclusive that spaces must be designed with anticipated readiness for expansion and expected influx of material accumulation. This includes the formalization of spaces such as the kitchen and laundry areas, optimized material specifications, optional furniture recommendations, and the inclusion of utility provisions for the new core unit.